The effect of consumer's need for uniqueness and emotional experience on brand pride: The mediating role of electronic word-of-mouth - Arshad, Sana (2023)
Brand pride generates positive emotions and increases brand loyalty, leading to more word-of- mouth advertising. It is necessary to emphasize the need to raise awareness of national cosmetics and promote beauty through simplicity and originality. This study investigates the effect of consumer’s need for uniqueness and emotional experience on brand pride with the mediating role of eWOM. Primary data was collected from 394 Pakistani millennials and analyzed using partial least squares structural equation modeling via Smart PLS 3.0. The findings indicate that consumers’ need for uniqueness and emotional experiences significantly influenced eWOM. In addition, eWOM had a positive impact on the mediation between the consumer need for uniqueness, emotional experience and brand pride. This study broadens the scope of WOM research in the digital age and sheds light on diverse customer interactions. It also uncovers the growing trend of organic cosmetics due to increased awareness of cruelty-free products and offers insights into men's cosmetic preferences. The proposed research framework integrates the theory of uniqueness and the theory of brand congruence to advance knowledge about consumer need for uniqueness, emotional experiences and the impact of eWOM on Pakistani millennials' brand pride. The results highlight the importance of eWOM in shaping consumer decisions and make the case for further industry research. The findings have significant implications for marketers and platform administrators in managing consumer responses. Categorizing viewpoints resolves conflicts while customizing beauty perceptions and pricing strategies to target specific groups. The research also provides guidance to platform operators on improving usability and encouraging reviews.